Pharmacokinetic Drug Interaction Between Amlodipine and Tadalafil: An Open-Label, Randomized, Multiple-Dose Crossover Study in Healthy Male Volunteers - Kim H; Lee SH; Jung J; Hong S; Lim HS (Dove Medical Press, 2022)
Hyungsub Kim,1 Shi Hyang Lee,2 Jina Jung,3 Sunghee Hong,3 Hyeong-Seok Lim2 1Department of Emergency Medical Services, College of Health Sciences, Eulji University, Seongnam, Republic of Korea; 2Department of Clinical Pharmacology and Therapeutics, Asan Medical Center, University of Ulsan, Seoul, Republic of Korea; 3Hanmi Pharmaceutical Co. Ltd., Seoul, Republic of KoreaCorrespondence: Hyeong-Seok Lim, Tel +82-2-3010-4613, Fax +82-2-3010-4623, Email mdlhs@amc.seoul.krPurpose: The combined administration of tadalafil, a phosphodiesterase-5 inhibitor, and amlodipine, a calcium channel blocker, can be a promising therapeutic option for hypertension patients with erectile dysfunction. This study aimed to examine the pharmacokinetic drug interaction between tadalafil and amlodipine and the tolerability of their combined administration in healthy male subjects.Subjects and Methods: Healthy volunteers (N = 24) were randomly assigned to one of the six sequences that consisted of three treatments: tadalafil (5 mg) alone, amlodipine (10 mg) alone, and tadalafil plus amlodipine. The study drugs were administered orally for 9 d, and the collected serial blood samples were analyzed up to 72 h after the last dosing. Pharmacokinetic parameters were calculated using non-compartmental analysis.Results: For tadalafil, geometric mean ratios (GMRs) (90% confidence interval (CI)) of the combined therapy over the monotherapy were 1.57 (1.46- 1.68) for AUCτ,ss and 1.34 (1.24- 1.45) for Cmax,ss. For amlodipine, the GMRs (90% CI) of AUCτ,ss and Cmax,ss were 0.93 (0.90- 0.97) and 0.95 (0.91- 0.99), respectively. The severity of all observed adverse events (AEs) related to the study drugs was mild, and the frequency of AEs of the combined administration was not significantly different from the monotherapy.Conclusion: A substantial pharmacokinetic drug interaction between tadalafil and amlodipine was observed with respect to the concentration of tadalafil when administered concomitantly. However, the dose range of the combined administration of tadalafil and amlodipine in the present study was well tolerated by the subjects.Keywords: drug interaction, tadalafil, amlodipine, pharmacokinetics, tolerability